Un malinconico nella commedia gottschediana. «Der Hypochondrist» di Theodor Johann Quistorp: [A melancholic in Gottsched’s anthology of comedy. Theodor Johann Quistorp’s «The hypochondriac»] (Studia theodisca, 2022)
Theodor Johann Quistorp was among the regular contributors to Gottsched’s Deutsche Schaubühne (1741-1745). In addition to his published works as a playwright, he tried his hand at writing non-fiction, taking a stand against Baumgarten’s theories, and engaging in a heated debate with Georg Friedrich Meier. Quistorp’s comedies are actually based on a conception of the comic effect that is far removed from Gottschedian rationalism. In his Hypochondrist (1745), melancholy and depression are not represented as evil and morally deviant, but as a physiological expression of human nature, which is to be linked to all other aspects of individual identity.